Saving by default: Evidence from a field experiment in rural India - Vincent Somville; Lore Vandewalle (Graduate Institute of International and Development Studies, 2015)
A growing share of the world population is getting access to a formal bank account. This allows a move from cash to account based payments. Grounding our hypothesis in behavioral economics, we conjecture that being paid on an account instead of in cash can play a major role in encouraging savings. When paid on the account, the money is saved by default, while - as long as payments are done in cash - the money is ready to be spent. We test our hypothesis in rural India, with villagers who either had an account, or were asked to open one. They received weekly payments of Rs 150 for about 10 consecutive weeks. We randomly allocated them to being paid on the account (treated) or in cash (control). We find that the treatment increases the account balance by about 110 percent, and that the effect is long lasting. The control villagers do not save more in other assets, but increase their expenditures on regular consumption items. We exclude two alternative mechanisms that could explain the result. First, using lab in the field games, we show that the treatment does not enhance the trust in or empathy towards the banker. Second, we provide evidence against the treated having developed an active savings habit on the account: they behave like the control, when we switch from account to cash payments.
Keywords: D14; C93; D03; G21; O16; 330; savings; finance; behavioral economics; default; India